Time-Varying Individual Risk Attitudes over the Great Recession: A Comparison of Germany and Ukraine - Thomas Dohmen; Hartmut Lehmann; Norberto Pignatti (Institute for the Study of Labor (IZA), 2015)
We use the panel data of the German Socio-Economic Panel (SOEP) and of the Ukrainian Longitudinal Monitoring Survey (ULMS) to investigate whether risk attitudes have primary (exogenous) determinants that are valid in different stages of economic development and in a different structural context, comparing a mature capitalist economy and a transition economy. We then analyze the stability of the risk measures over time. Between 2007 and 2012 we have the Great Recession, which had a mild impact in the German labor market while it had a more profound impact on the Ukrainian labor market. This enables us to investigate whether and how the crisis impacted on the risk attitudes in the two countries. By focusing on self-employment we also investigate whether the reduced willingness to take risks as a consequence of the Great Recession affects labor market dynamics and outcomes.
Keywords: J64; J65; P50; 330; labor market outcomes; time variation; Great Recession; risk attitudes; Germany; Ukraine